CONCEPTUAL VARIATIONS ON READING COMPREHENSION THROUGH HIGHER ORDER THINKING SKILLS (HOTS) STRATEGY - Nani Ronsani Thamrin; Silvia Agustin (English Review: Journal of English Education, 2019)
Thinking capability is the most significant aspect in educational process and as every students has their own distinctive method in thinking will posses their learning concepts. Being a critical thinker means they have to be able to think more critical than any other people, by practicing their skills through comprehending the material and the content of the text. Therefore, This paper discussed the phenomenon of conceptual variations on reading comprehension through Higher Order Thinking Skill (HOTS) strategy in Kuningan University and describes how the HOTS strategy improve the students’ skills in comprehending the academic reading text. The data collected by using a classroom observation and interview with students, were analyzed qualitatively by using categories formulated based on theories related HOTS stategy. As a result, the author obtains the various concepts on reading comprehension seen from the C1-C6 phase of HOTS strategy and critical reading. This indicates that the most of students have higher order thinking skills in comprehending the text in critical reading class. The findings are expected to be references for English teachers in the implementation of teaching strategy.